Organisational factors affecting employee engagement in the service industry in Malaysia - Fung, Xin Ming; Wong, Wen Lin; Yap, Yi Wen (2024)
This study is structured into five chapters, each offering a different perspective. These chapters cover the research overview, literature review, research methodology, data analysis, discussion, implications and conclusion of the study. The research explores explicitly how factors such as the supervisor support, organisational trust, and work life balance influence employee engagement in Malaysian service industry. To support our investigation, we reviewed various past studies and collected new data from over 387 respondents through survey questionnaires. Our focus was on understanding the impact of these factors on employee engagement and how they influence the relationship between the independent and dependent variables. We employed multiple analytical methods to interpret the results. Towards the end of the paper, we provide several practical recommendations for future research and discuss the limitations we faced during our study. Additionally, an example of the survey questionnaire used for data collection is included in the appendix.